Physicochemical assessment and bioactive properties of condensed distillers solubles, a by-product from the sorghum bio-fuel industry. (November 2016) - Navarro, Marta; Sonni, Francesca; Chaliha, Mridusmita; Netzel, Gabi; Stanley, Roger; Sultanbawa, Yasmina
Abstract: Large volumes of condensed distillers solubles (CDS) are generated as by-products, from the sorghum bioethanol industry. The objective was to assess the physico-chemical and bioactive properties of CDS. The unfractionated CDS showed the highest content of phenolic compounds (16 mg GAE/g), antioxidant (522 μM Trolox/g) and antimicrobial activity (MIC 1%(w/v) against Campylobacter spp.) compared to its extracts. The water and methanol extracts also showed high levels of phenolic compounds and antioxidant activity (11.6 and 9.2 mg GAE/g and 349 and 409 μM Trolox/g respectively), followed by ethanol and acetone extractions (7.5 and 6.6 mg GAE/g; 337 and 346 μM Trolox/g respectively). A positive correlation was revealed between total phenol and antioxidant activity. The main phenolic compounds found in the extracts were protocatechuic acid, 4-hydroxybenzoic acid, taxifolin, ferulic acid, cinnamic acid and p -coumaric acid. This study indicates the potential of using CDS as a functional ingredient for other food and feed applications. Highlights: Peptides in Condensed Distillers Solubles (CDS) had antimicrobial activities. Water extract of CDS had the most potent bioactive properties. Correlations were found between total phenol content and antioxidant activity. Sorghum grain CDS had high levels of phytochemicals.